Vorinostat plus tacrolimus/methotrexate to prevent GVHD after myeloablative conditioning, unrelated donor HCT - Choi, Sung Won (Blood, 2017)
The oral histone deacetylase (HDAC) inhibitor (vorinostat) is safe and results in low incidence of acute graft-versus-host disease (GVHD) after reduced-intensity conditioning, related donor hematopoietic cell transplantation (HCT). However, its safety and efficacy in preventing acute GVHD in settings of heightened clinical risk that use myeloablative conditioning, unrelated donor (URD), and methotrexate are not known. We conducted a prospective, phase 2 study in this higher-risk setting. We enrolled 37 patients to provide 80% power to detect a significant difference in grade 2 to 4 acute GVHD of 50% compared with a reduction in target to 28%. Eligibility included adults with a hematological malignancy to receive myeloablative HCT from an available 8/8-HLA matched URD. Patients received GVHD prophylaxis with tacrolimus and methotrexate. Vorinostat (100 mg twice daily) was started on day −10 and continued through day +100 post-HCT. Median age was 56 years (range, 18-69 years), and 95% had acute myelogenous leukemia or high-risk myelodysplastic syndrome. Vorinostat was safe and tolerable. The cumulative incidence of grade 2 to 4 acute GVHD at day 100 was 22%, and for grade 3 to 4 it was 8%. The cumulative incidence of chronic GVHD was 29%; relapse, nonrelapse mortality, GVHD-free relapse-free survival, and overall survival at 1 year were 19%, 16%, 47%, and 76%, respectively. Correlative analyses showed enhanced histone (H3) acetylation in peripheral blood mononuclear cells and reduced interleukin 6 (P = .028) and GVHD biomarkers (Reg3, P = .041; ST2, P = .002) at day 30 post-HCT in vorinostat-treated subjects compared with similarly treated patients who did not receive vorinostat. Vorinostat for GVHD prevention is an effective strategy that should be confirmed in a randomized phase 3 study. This trial was registered at www.clinicaltrials.gov as #NCT01790568.